Aftereffects in Epigenetic Age Related to Cognitive Decline and Inflammatory Markers in Healthcare Personnel with Post-COVID-19: A Cross-Sectional Study - Nolasco-Rosales GA; Alonso-García CY; Hernández-Martínez DG; Villar-Soto M; Martínez-Magaña JJ; Genis-Mendoza AD; González-Castro TB; Tovilla-Zarate CA; Guzmán-Priego CG; Martínez-López MC; Nicolini H; Juárez-Rojop IE (International Journal of General Medicine, 2023)
Germán Alberto Nolasco-Rosales,1,* Cecilia Yazmin Alonso-García,1,* David Gustavo Hernández-Martínez,1 Mario Villar-Soto,2 José J Martínez-Magaña,3 Alma Delia Genis-Mendoza,4 Thelma Beatriz González-Castro,5 Carlos Alfonso Tovilla-Zarate,6 Crystell Guadalupe Guzmán-Priego,1 Mirian Carolina Martínez-López,1 Humberto Nicolini,7 Isela Esther Juárez-Rojop1 1División Académica de Ciencias de la Salud, Universidad Juarez Autónoma de Tabasco, Villahermosa, Tabasco, México; 2Hospital Regional de Alta Especialidad de Salud Mental, Villahermosa, Tabasco, México; 3Department of Psychiatry, Yale University School of Medicine, New Haven, CT, USA; 4Hospital Psiquiátrico Infantil “Dr. Juan N. Navarro”, Ciudad de México, México; 5División Académica Multidisciplinaria de Jalpa de Méndez, Universidad Juarez Autónoma de Tabasco, Jalpa de Méndez, Tabasco, México; 6División Académica Multidisciplinaria de Comalcalco, Universidad Juarez Autónoma de Tabasco, Comalcalco, Tabasco, México; 7Departamento de Genética Psiquiátrica, Instituto Nacional de Medicina Genómica (INMEGEN), Ciudad de México, México*These authors contributed equally to this workCorrespondence: Isela Esther Juárez-Rojop, División Académica de Ciencias de la Salud, Universidad Juarez Autónoma de Tabasco, Av. Gregorio Méndez 2838-A, Col. Tamulté, Villahermosa, 86100, México, Email iselajuarezrojop@hotmail.com Humberto Nicolini, Instituto Nacional de Medicina Genómica (INMEGEN), Ciudad de México, 86100, México, Email hnicolini@inmegen.gob.mxPurpose: Epigenetic age and inflammatory markers have been proposed as indicators of severity and mortality in patients with COVID-19. Furthermore, they have been associated with the occurrence of neurological symptoms, psychiatric manifestations, and cognitive impairment. Therefore, we aimed to explore the possible associations between epigenetic age, neuropsychiatric manifestations and inflammatory markers (neutrophil-lymphocyte ratio [NLR], platelet-lymphocyte ratio [PLR], monocyte-lymphocyte ratio [MLR], and systemic immune-inflammation index [SII]) in healthcare personnel with post-COVID condition.Patients and Methods: We applied the Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE) tests to 51 Mexican healthcare workers with post-COVID-19 condition; we also estimated their epigenetic age using the PhenoAge calculator.Results: The participants had a post-COVID condition that lasted a median of 14 months (range: 1– 20). High NLR (> 1.73) had association with mild cognitive impairment by MMSE (p=0.013). Likewise, high MLR (> 0.24) were associated with language domain in MOCA (p=0.046). Low PLR (< 103.9) was also related to delayed recall in MOCA (p=0.040). Regarding comorbidities, hypertension was associated with SII (p=0.007), overweight with PLR (p=0.047) and alcoholism was associated with MLR (p=0.043). Interestingly, we observed associations of low PLR (< 103.9) and low SII (< 1.35) levels with increased duration of post-COVID condition (p=0.027, p=0.031). Likewise, increases in PhenoAge were associated with high levels of SII (OR=1.11, p=0.049), PLR (OR=1.12, p=0.035) and MLR (OR=1.12, p=0.030).Conclusion: We observed neurocognitive changes related to inflammatory markers and increases in epigenetic age in healthcare personnel with post-COVID-19 condition. Future research is required to assess mental and physical health in individuals with post-COVID-19 symptoms.Keywords: post-COVID-19, cognitive manifestation, inflammatory markers, epigenetic age